PENGARUH PUPUK ORGANIK BERKADAR BESI TINGGI TERHADAP PERTUMBUHAN DAN PRODUKSI PADI SAWAH - Triyani Dewi; Iswandi Anas; - Suwarno; Dedi Nursyamsi (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2013)
The application of chemical fertilizers is costly and gradually lead to the environmental problems. Organic residue recycling is becoming an increasingly important aspect of environmentally sound sustainable agriculture. Organic content of these soils are mostly very low, while it is widely know that organic matter is very important to keep physical, chemical, and biological properties of soil as well as soil productivity. The objectives of the study were to know effect of organic fertlizer that high iron content on growth and production paddy rice. Pot experiment was conducted on May to November 2011 in green house. This experiment using a randomized complete block design with two factors; the types of soil (Endoaquert, Tropaquept, and Hapludult) and organic fertilizerenriched with Fe (FeCl3) in various level. Each treatment was replicated three times. The results showed that the organic fertilizer enriched with iron up to 64000 mg.kg-1 didn’t significantly effect on the growth and rice production. Application of organic fertilizer in Tropaquept Sukamandican increase significantly on height plant, number of tiller, dry weight of grain and 1000-grain weight.